Did the alcohol prohibition reduce motor vehicle accidents related to alcohol? : - Brabenec, Tomáš (2015)
This paper tries to find out whether a short ban on sales of liquors reduced the harmful use of alcohol with respect to motor vehicle accidents. I make use of short (two weeks) alcohol prohibition which was imposed by the Ministry of Health Care in the Czech Republic in September 2012 aiming to stop the deadly wave of methanol poisoning. To estimate the effect of prohibition on the number of road traffic accidents, I exploit the methodology of differences-in-differences. I use daily data about traffic accidents from the Czech Republic (treatment group) and from neighboring countries such as Austria, Germany and Poland (control group). The result suggests that there is no significant drop in term of road traffic accidents.